Newly discovered anthropomorphic Stone Statue fromterritory of Khӧvsgӧl aimag - Batsuuri, Ankhbayar; Jamsanjav, Bayarsaikhan; Ganbold, Ankhsanaa (Studia Archaeologica, 2022)
In 2020, these 3 anthropomorphic stone stelae and their ritual components were registered and documented during the fieldwork to rescue very rare and valuable historical finds of the Bronze and Early Iron Ages which were randomly found by local people in Khӧvsgӧl aimag. It was able to date these anthropomorphic stones back to the time of the ancient Tureg Khaganate of Inner Asia based on their form, depictions, and compositions. One of them is clearly representing that the monument for the high-ranking person in terms of components such as a stone box, an earthen wall, and a line of standing stones as known as balbal. This pilot study will help to clarify the issues of early medieval history and culture in the northern part of Mongolia. Хөвсгөл аймгийн нутгаас шинээр илрүүлсэн хүн чулууд Товчлол. 2020 онд Хөвсгөл аймгийн нутгаас иргэдийн санамсаргүй олсон олдворууд хүрэл, төмрийн түрүү үеийн ховор, түүхийн үнэт дурсгал болох нь тодорхой болсон тул тэдгээрийн олдсон газрыг нарийвчлан нягтлан судлах зайлшгүй авран хамгаалах ажлын явцад 3 хүн чулуу, тахилын онгоныг бүртгэн баримтжууллаа. Тэдгээр хүн чулуудын дүрслэл, дүр байдал, бүрэлдэхүүн нь Эртний Түрэгийн хаант улсын үед холбогдож байна. Зарим хүн чулуунд чулуун хашлага, шороон хэрэм, зэл чулуу бүхий тахилын онгонтой тул өндөр язгууртай хүнд зориулсан дурсгал болохыг илтгэж байлаа. Дээрх хэрэглэгдэхүүн Монгол орны умар нутаг дахь дундад эртний түүх соёлын асуудлуудыг тодруулахад нэмэр болох нь дамжиггүй. Түлхүүр үгс: Хөвсгөл аймаг, хүн чулуу, түрэг